A major plant practice at the Food People, Incorporated RIS Industrial Complex, Bo. Tabe, Guiguinto, Bulacan - Sabado, Charizel Almacen (2007)
As part of the curriculum for the Bachelor of Science in Food Technology, a plant practice was conducted at The Food People, Incorporated from April to May 2006. The 288 hours of plant practice aimed to provide the intern with ample exposure on the plant?s processing and production lines. The trainee was able to gather information regarding the company?s description, existing product listing, raw material handling, processing system, and quality control and assurance system. This manuscript documents the information collected from the internship, the technical analyses on some features of the company, and the problems encountered during the training to which recommendations were given
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2007
Keywords: Ice cream; Ice cream processing; Ice cream -- Production planning; Ice cream -- Production control; Ice cream -- Composition